Mapping out the use of social media by members of the clothing industry from Alto Vale do Itajaí (ModaPalavra e-periódico, 2015)
This article’s goal was to map out the use of social media by the clothing industry from Alto Vale do Itajaíby means of a qualitative-quantitative research. The research field consists of 43 enterprises associated to the local trades union (Sindicato das Indústrias da Fiação, Tecelagem, Confecção e Vestuários do Alto Vale do Itajaí) and 5 non-affiliated, but considered regionally significant. By analyzing the mapping’s results, the authors were able to verify the viability of communication strategies’ definitions and the possibility of proposing a digital strategic plan for design management to the local companies, that have been poorly exploring social media. Although there is already perceived awareness of its importance, there’s also a noticeable lack of professionalism in this area. Therefore, this appears to be a fantastic field to be harvested by qualified professionals, who can create and define communication and marketing strategies and, altogether, work with design management.
Keywords: social media; design management; social media strategy planning process